2015
DOI: 10.1007/s12154-015-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Standard fluorescent proteins as dual-modality probes for correlative experiments in an integrated light and electron microscope

Abstract: Integrated light and electron microscopes (ILEMs) will enable a new generation of high-precision correlative imaging experiments. To fully exploit these systems, samples must contain dual-modality probes that highlight the position of macromolecules in the context of cell ultrastructure. We demonstrate that the fluorescent proteins (FPs) GFP (green), YFP (yellow) and mCherry can be used as dualmodality probes for ILEM when preserved using the inresin fluorescence (IRF) technique, which delivers stable active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…2 , step 2). Fluorescent cells were located using the SECOM light microscope in WF mode within the SEM at 200 Pa partial pressure of water vapour, which we previously demonstrated to be optimal for WF imaging in vacuo ( Brama et al, 2015 ). The laser power was increased to a density of 330 W/cm 2 , to drive FP blinking, and sequences of ∼30,000 images were collected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , step 2). Fluorescent cells were located using the SECOM light microscope in WF mode within the SEM at 200 Pa partial pressure of water vapour, which we previously demonstrated to be optimal for WF imaging in vacuo ( Brama et al, 2015 ). The laser power was increased to a density of 330 W/cm 2 , to drive FP blinking, and sequences of ∼30,000 images were collected.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that YFP and GFP are photostable when embedded in acrylic resins using an in-resin fluorescence (IRF) protocol. Conservation of the hydration state of the FPs was critical for stable, long-lived fluorescence, and also for imaging ultrathin IRF sections in vacuo using an integrated light and scanning electron microscope (ILSEM) ( Brama et al, 2015 , Peddie et al, 2014 ). Fluorescence and electron images of ultrathin IRF sections are unique in that the information from both imaging modalities is gathered from the same physical slice (50–200 nm thick).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that GFP maintains bioluminescence well in the water solution, while an isolated chromophore placed in vacuum or in bulk water condition cannot sustain fluorescence. [30][31][32] Interestingly, it has been found that the chromophore alike molecules, after being suppressed with the dihedral flexibilities, become fluorescent in standalone conditions. 33,34 Hence, inhibition of the dihedral fluctuations of the chromophore appears to be crucial for maintaining the GFP fluorescence function.…”
Section: Discussionmentioning
confidence: 99%
“…imaging (Agronskaia et al, 2008;Faas et al, 2013;Zonnevylle et al, 2013;Vidavsky et al, 2014;Brama et al, 2015;de Boer et al, 2015, among others). We describe, to our knowledge, the first application of iCLEM for geological materials, utilizing simultaneous fluorescence and SEM to image sedimentary organic matter in shale, including an immature oil shale from the Eocene Green River Mahogany Zone, Colorado, USA, and from mid-oil window paralic shale of the Upper Cretaceous Tuscaloosa Group, southern Mississippi, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Correlative light and electron microscopy (CLEM) techniques are widely applied in cellular biology (Polishchuk et al ., ; Sartori et al ., ; de Boer et al ., ). Integrated CLEM (iCLEM) techniques, where both imaging modalities are performed sequentially in the same instrument without sample transfer, have also been used in biology and biomedical imaging (Agronskaia et al ., ; Faas et al ., ; Zonnevylle et al ., ; Vidavsky et al ., ; Brama et al ., ; de Boer et al ., , among others). We describe, to our knowledge, the first application of iCLEM for geological materials, utilizing simultaneous fluorescence and SEM to image sedimentary organic matter in shale, including an immature oil shale from the Eocene Green River Mahogany Zone, Colorado, USA, and from mid‐oil window paralic shale of the Upper Cretaceous Tuscaloosa Group, southern Mississippi, USA.…”
Section: Introductionmentioning
confidence: 99%